2022
DOI: 10.1186/s12912-022-00956-5
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting males to the nursing profession: acceptability testing of the ‘Make a Difference with Nursing’ intervention for post-primary school students

Abstract: Background The nursing profession is facing a worldwide recruitment shortage which could be partially addressed by recruiting more males. However, in many developed countries numbers of male nurses have traditionally been low. To address this issue we developed and tested a post-primary school-based intervention to recruit more males into the nursing profession. Methods Participants included thirty-four  female students drawn from an all-girls post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The results demonstrate positive changes in students' perceptions across the domains of self-efficacy, job prospects and social influences, indicating that the serious game intervention did impact on how participants viewed the nursing and midwifery professions. The findings align with previous research on interventions aimed at altering perceptions of healthcare professions, emphasising the potential of innovative approaches like serious games in reshaping attitudes [29][30][31].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results demonstrate positive changes in students' perceptions across the domains of self-efficacy, job prospects and social influences, indicating that the serious game intervention did impact on how participants viewed the nursing and midwifery professions. The findings align with previous research on interventions aimed at altering perceptions of healthcare professions, emphasising the potential of innovative approaches like serious games in reshaping attitudes [29][30][31].…”
Section: Discussionsupporting
confidence: 86%
“…This effect of school type was seen in addition to gender differences as those attending an allgirls school also scored higher than females who attended a mixed-gender school. This observation concords with another study which employed the 'Nursing as a Career Choice Questionnaire' [27] to assess their 'Make a Difference with Nursing' intervention among post-primary school students [29]. While the precise reason for this discrepancy remained unclear, the authors suggested that career's teachers at an all-girls school may be more likely to discuss nursing and midwifery careers with their students, possibly due to the traditionally female dominated nature associated with nursing careers [35].…”
Section: Discussionmentioning
confidence: 84%